Cover Image. Issue 4 (8th August 2018) - Sun, Yang; Yao, Yuting; Fan, Yawen; Su, Junwei; Luo, Zhaoyang; Lan, Peng; Bao, Yan
Abstract : The cover image, by Yang Sun et al., is based on the Research Article Gas‐water energy conversion efficiency in two‐phase vertical downflow, DOI: 10.1002/ese3.200 .